Pendekatan Problem Solving Bhabinkamtibmas Dalam Pembinaan Keamanan Dan Ketertiban Masyarakat Di Desa Bunder Kecamatan Susukan Kabupaten Cirebon - Abdul Wahid Wahid; Galih Rinenda Putra (Fakultas Hukum Universitas Mulawarman, 2021)
Forms of law violations that often occur are minor persecution, fights, and others. Violations of these laws can cause conflicts and disturbances for others and can lead to clashes between groups. This type of research is qualitative research, using a field research approach, producing descriptive data in the form of the Bhabinkamtibmas Problem Solving Approach in Community Security and Order Development. The purpose of this study was to determine the problem-solving approach of Bhabinkamtibmas in fostering security and public order in Bunder Village, Susukan District, Cirebon Regency. The results of this study are that Bhabinkamtibmas supervises the settlement of criminal acts of persecution through penal mediation at the Susukan Police Station and provides a place for the litigants to negotiate to obtain a peace agreement. The settlement of criminal acts of persecution through penal mediation at the Susukan Police, Cirebon Regency can only be done once. Perpetrators of criminal acts of persecution whose cases have been resolved by penal mediation and if they repeat the crime will be processed according to the applicable laws and regulations until the judicial stage, provided that investigators attach evidence of a statement made by the perpetrator of the crime. Keywords: Approach; Problem Solving; Bhabinkamtibmas